“Dream Away the Time”. Metric Play in Benjamin Britten’s A Midsummer Night’s Dream - McGartland, Aidan (Revue musicale OICRM, 2025)
This article examines how meter serves as a key compositional device in Benjamin Britten’s A Midsummer Night’s Dream (1960), employed in strikingly idiosyncratic ways. Borrowing Leccia’s (2024) notion of “play” as an analytical metaphor, I explore Britten’s diverse metric types and techniques through representative excerpts. Drawing on the metric theories of Lerdahl and Jackendoff (1983) and Rothstein (1989), alongside key Britten scholarship by Rupprecht (2001), I adapt multiple analytical approaches to account for the opera’s stylistic mélange. Four main findings emerge. First, each of the three character groups (fairies, lovers, and rustics) possesses a distinct musical characterisation, including through meter. Second, Britten employs a variety of meters and hypermeters, often integrating irregular rhythms within the larger structure. Third, he manipulates meter and hypermeter to establish models before deviating, typically for narrative effect. Finally, hypermeter interacts with grouping to generate tonal phrases and static atonal hypermetric units.